Pyrodiversity begets plant–pollinator community diversity. (29th February 2016) - Ponisio, Lauren C.; Wilkin, Kate; M'Gonigle, Leithen K.; Kulhanek, Kelly; Cook, Lindsay; Thorp, Robbin; Griswold, Terry; Kremen, Claire
Abstract: Fire has a major impact on the structure and function of many ecosystems globally. Pyrodiversity, the diversity of fires within a region (where diversity is based on fire characteristics such as extent, severity, and frequency), has been hypothesized to promote biodiversity, but changing climate and land management practices have eroded pyrodiversity. To assess whether changes in pyrodiversity will have impacts on ecological communities, we must first understand the mechanisms that might enable pyrodiversity to sustain biodiversity, and how such changes might interact with other disturbances such as drought. Focusing on plant–pollinator communities in mixed‐conifer forest with frequent fire in Yosemite National Park, California, we examine how pyrodiversity, combined with drought intensity, influences those communities. We find that pyrodiversity is positively related to the richness of the pollinators, flowering plants, and plant–pollinator interactions. On average, a 5% increase in pyrodiversity led to the gain of approximately one pollinator and one flowering plant species and nearly two interactions. We also find that a diversity of fire characteristics contributes to the spatial heterogeneity ( β ‐diversity) of plant and pollinator communities. Lastly, we find evidence that fire diversity buffers pollinator communities against the effects of drought‐induced floral resource scarcity. Fire diversity is thus important for the maintenance of flowering plant and pollinator diversity and predicted shifts in fire regimes to include less pyrodiversity compounded with increasing drought occurrence will negatively influence the richness of these communities in this and other forested ecosystems. In addition, lower heterogeneity of fire severity may act to reduce spatial turnover of plant–pollinator communities. The heterogeneity of community composition is a primary determinant of the total species diversity present in a landscape, and thus, lower pyrodiversity may negatively affect the richness of plant–pollinator communities across large spatial scales.